2007
DOI: 10.1182/blood-2006-10-051086
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenomic analysis of acute promyelocytic leukemia cells highlights CYP26 cytochrome metabolism in differential all-trans retinoic acid sensitivity

Abstract: Disease relapse sometimes occurs after acute promyelocytic leukemia (APL) therapy with all-trans retinoic acid (ATRA). Among the diagnostic parameters predicting relapse, heterogeneity in the in vitro differentiation rate of blasts is an independent factor. To identify biologic networks involved in resistance, we conducted pharmacogenomic studies in APL blasts displaying distinct ATRA sensitivities. Although the expression profiles of genes invested in differentiation were similarly modulated in low-and high-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…It is thus tempting to speculate that patients, which underwent first-line therapy and feature low tumor burden could profit from ATRA therapy (41). In addition, it cannot be excluded that some tumor cells might be endowed with an ATRA-resistant phenotype caused by ATRA-metabolizing enzymes, which are culprits of ATRA resistance in other tumor entities (42,43). Further, loss of RARs in a fraction of tumor cells, which occurs as a common event in several extracranial cancers (44)(45)(46), could render cells irresponsive to ATRA effects and require long-term, supraphysiologic ATRA doses.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus tempting to speculate that patients, which underwent first-line therapy and feature low tumor burden could profit from ATRA therapy (41). In addition, it cannot be excluded that some tumor cells might be endowed with an ATRA-resistant phenotype caused by ATRA-metabolizing enzymes, which are culprits of ATRA resistance in other tumor entities (42,43). Further, loss of RARs in a fraction of tumor cells, which occurs as a common event in several extracranial cancers (44)(45)(46), could render cells irresponsive to ATRA effects and require long-term, supraphysiologic ATRA doses.…”
Section: Discussionmentioning
confidence: 99%
“…RA is known to induce a temporal program of HOX gene expression and this expression is often perturbed in leukemias. 25,[41][42][43][44] Of note, the miR-10b, which is potentially repressed by PML-RARA (Table 1 and Figure 1D), also regulates HOXD10. 45 The up-regulation of HOX genes in AML due to the downregulation of miRNAs has already been suspected 26,46,47 but we revealed here a potential link with oncogene-mediated transcriptional repression at least in the case of APL.…”
Section: Discussionmentioning
confidence: 99%
“…The blast cells were treated with 100 nM ATRA for 6 days and RNA extraction was performed each day from day 0 to day 4 of treatment. 24,25 Cell viability and maturation of APL cells was assessed by trypan blue ( Figure 4A) and NitroBlueTetrazolium (NBT) dye reduction assays ( Figure 4B), respectively, at days 0, 3, and 6 of ATRA treament. We also controlled the induction of the prototypic RARB by ATRA ( Figure 4C).…”
Section: Transcriptional Repression Of the Mir-210 And The Mir23a/24-mentioning
confidence: 99%
See 1 more Smart Citation
“…By TUNEL assay, the increase of apoptosis was not observed in ATRA-treated MPM tumour cells in mice compared with untreated mice (data not shown). Next, we examined the mRNA expression of CYP26A1 [32], a retinoic acid regulated gene, by real-time RT-PCR, and found that mRNA levels of CYP26A1 were decreased in ATRAtreated MPM tumour cells in mice compared with untreated mice, which suggested an increased amount of active retinoic acid, namely, an autoregulation feedback loop (data not shown). However, it is not clear whether the observed effect is specific to retinoic acid signalling.…”
Section: Discussionmentioning
confidence: 99%